Talking about human papillomavirus and cancer: development of consultation guides through lay and professional stakeholder coproduction using qualitative, quantitative and secondary data. Issue 6 (26th June 2017) - Hendry, Maggie; Pasterfield, Diana; Gollins, Simon; Adams, Richard; Evans, Mererid; Fiander, Alison; Robling, Michael; Campbell, Christine; Bekkers, Marie-Jet; Hiscock, Julia; Nafees, Sadia; Rose, Janice; et al.
Abstract : Background: High-risk human papillomaviruses (HPVs) cause all cervical cancer and the majority of vulvar, vaginal, anal, penile and oropharyngeal cancers. Although HPV is the most common sexually transmitted infection, public awareness of this is poor. In addition, many clinicians lack adequate knowledge or confidence to discuss sexual transmission and related sensitive issues. Complex science needs to be communicated in a clear, digestible, honest and salient way. Therefore, the aim of this study was to coproduce with patients who have cancer appropriate resources to guide these highly sensitive and difficult consultations. Methods: A matrix of evidence developed from a variety of sources, including a systematic review and telephone interviews with clinicians, supported the production of a draft list of approximately 100 potential educational messages. These were refined in face-to-face patient interviews using card-sorting techniques, and tested in cognitive debrief interviews to produce a ‘fast and frugal’ knowledge tool. Results: We developed three versions of a consultation guide, each comprising a clinician guidance sheet and patient information leaflet for gynaecological (cervical, vaginal, vulvar), anal or oropharyngeal cancers. That cancer could be caused by a sexually transmitted virus acquired many years previously was surprising to many and shocking to a few patients. However, they found the information clear, helpful and reassuring. Clinicians acknowledged a lack of confidence in explaining HPV, welcomed the clinician guidance sheets and considered printed information for patients particularly useful. Conclusion: Because of the ‘shock factor’, clinicians will need to approach the discussion of HPV with sensitivity and take individual needs and preferences into account, but we provide a novel, rigorously developed and tested resource which should have broad applicability in the UK National Health Service and other health systems.